Ministerial participation critical for addressing global noncommunicable disease agenda: Highlights of ministerial forum - J S Thakur (International Journal of Noncommunicable Diseases, 2017)
In view of achieving the Sustainable developmental goals by 2030 and preparation for UN high-level meeting 2018, the Ministerial forum was the key session of the World noncommunicable disease (NCD) Congress 2017 with the participation of Ministers, Parliamentarians, and Policymakers from different parts of the World. The purpose of forum was to set a platform for a wide range of high-level policy issues for the prevention and control of NCDs, discussion on implementation challenges and global action plan. Forum discussed and finalized the consensus statement “Chandigarh Declaration on NCDs” at the conclusion of the Congress.